The ground beetle genus Zuphium and subgenus Chlaenius (Trichochlaenius) (Coleoptera: Carabidae) from Iran, with the description of two new species - Mofrad, Farhad Eshraghi; Muilwijk, Jan; Talebi, Ali Asghar; Serri, Sayeh (Zootaxa, 2025)
Two new species of ground beetle from Iran are described and illustrated. Zuphium seiedyae sp. nov., collected from the Zagros Mountains in the Fars Province, and Chlaenius (Trichochlaenius) shimbarensis sp. nov., found in Khuzestan Province, are presented with detailed morphological descriptions and illustrations. In addition, identification keys and images of all Iranian species are provided. The country record for Chlaenius (T.) gotschii Chaudoir, 1846 is corrected from Iran in Azerbaijan, Chlaenius (T.) albissoni Reitter, 1908 is recorded for the first time from Jordan.